Respostas

2014-03-09T10:51:24-03:00
4 + 15y = 7
x
7x - 9y = 11

Sistema de equação:
Vamos resolver pelo método de substituição:
4 = 7 - 15y
x
x =     4          
      7 - 15y

7 (     4     ) - 9y = 11
     7 - 15y

   28      - 9y = 11
7 - 15y

28 - 9y (7- 15y) = 11 (7 - 15y)
28 - 63y + 135y² = 77 - 165y
135y² - 63y + 165y + 28 - 77 = 0
135y² + 102y - 49 = 0

a = 135                 b = 102                   c = - 49
Δ = b² - 4ac
Δ = 102² - 4 * 135 * (- 49)
Δ = 10404 + 26460
Δ = 36864

y = - b ± √Δ
     ---------------
         2a
y = - 102 ± √38864
     -----------------------
            2 * 135
y = - 102 ± 192
     -------------------
            270
y' = - 102 + 192 
          270
y' = 90 
÷ 270
y' = 1/3

y" = - 102 - 192 
            270
y" = - 294 ÷ 270
y" = - 49/45

Valor de x:
x =     4     
      7 - 15y

x' =      4          
      7 - 15 (1)
                 3
x' =    4      
      7 - 15
            3
mmc (1, 3) = 3
x' =         4          
          21 - 15
              3
x' =    4      
         6
         3
x' = 4 ÷ 2
x' = 2

x" =       4          
       7 - 15 (- 49)
                   45
x" =     4      
       7 + 735
              45
mmc (1, 45) = 45
x" =        4           
          315 + 735
               45
x" =    4 ÷ 70  
                 3
x" = 4 *  3  
            70
x" = 12 ÷ 70
x" = 6/35

Resposta: 
Temos dois resultados para x e y:
1º resultado: {2; 1/3}
2º resultado: {6/35; - 49/45}